Assessing the viability of the ACT natural gas distribution network for reuse as a hydrogen distribution network. (31st March 2021) - Gaykema, E.W.; Skryabin, I.; Prest, J.; Hansen, B.
Abstract: The Australian Capital Territory (ACT) has legislated and aims to be net zero emissions by 2045. Such ambitious targets have implications for the contribution of hydrogen and its storage in gas distribution networks Therefore, we need to understand now the impacts on the gas distribution network of the transition to 100% hydrogen. Assessment of the viability of decarbonising the ACT gas network will be partly based on the cost of reusing the gas network for the safe and reliable distribution of hydrogen. That task requires each element of the natural gas safety management system to be evaluated. This article describes the construction of a test facility in Canberra, Australia used to identify issues raised by 100% hydrogen use in the medium pressure distribution network, consisting of nylon and polyethylene (PE) as a means of identifying measures necessary to ensure ongoing validity of the network's regulatory safety case. Evoenergy (the ACT's gas distribution company) have constructed a Test Facility, incorporating an electrolyser, a gas supply pressure reduction and mixing skid a replica gas network and a domestic installation with gas appliances. Jointly with Australian National University (ANU) and Canberra Institute of Technology (CIT) the Company has commenced a program of "bench testing", initially with 100% hydrogen to identify gaps in the safety case specifically focusing on the materials, work practices and safety systems in the ACT. The facility is designed to assess:   Materials in use including aged network materials and components   Construction and installation techniques both greenfield and live gas work   Purging and filling techniques   Leak detection both underground and above ground   Emergency response and make safe techniques   Issues associated with use of hydrogen in light commercial and domestic appliances. To educate and train:   Technicians and gas fitters on infrastructure installation and management   Emergency response services on responding to hydrogen related emergencies in a network environment; and   manage public perceptions of hydrogen in a network environment. Australia has an enviable safety record for the safe and reliable transport, distribution and use of natural gas. The ACT natural gas network owned and operated by Evoenergy is one of the newest in Australia and has leveraged off the best materials and practices in Australia to build its network. The paper addresses major safety issues relating to the production/storage, distribution and consumer end use of hydrogen injected into existing gas distribution networks. The analysis is guided by the Safety Management System. The Hydrogen Testing Facility described in the paper provide tools for evaluation of hydrogen safety matters in the ACT and Australia-wide. Testing to date has confirmed that polyethylene and nylon pipe and their respective jointing techniques can contain 100% hydrogen at pressures used for the distribution of natural gas. Testing has also confirmed that current installation work practices on polyethylene and nylon pipe and joints are suitable for hydrogen service. This finding is subject to variation attributable to staff training and skill levels and further testing has been programmed as outlined in this paper. Testing of gas isolation by clamping and simulated repair on the hydrogen network has established that standard natural gas isolation techniques work with 100% hydrogen at natural gas pressures. Highlights: World first leak testing of hydrogen impact on nylon distribution pipe. Leak testing of hydrogen on nylon and polyethylene pipe under real world conditions. Testing of existing gas distribution work practices for safe use with hydrogen. Testing each element of a gas Safety Management System for safe use with hydrogen.